2012
DOI: 10.1073/pnas.1212887109
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid amide hydrolase ablation promotes ectopic lipid storage and insulin resistance due to centrally mediated hypothyroidism

Abstract: Fatty acid amide hydrolase (FAAH) knockout mice are prone to excess energy storage and adiposity, whereas mutations in FAAH are associated with obesity in humans. However, the molecular mechanism by which FAAH affects energy expenditure (EE) remains unknown. Here we show that reduced energy expenditure in FAAH −/− mice could be attributed to decreased circulating triiodothyronine and thyroxine concentrations secondary to reduced mRNA expression of both pituitary thyroid-stimulating hormone and hypothalamic thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 38 publications
1
24
1
Order By: Relevance
“…Of note, our finding that elevations of NAEs in the liver corresponded with slightly increased resting energy expenditure contrasts with a recent study that found decreased resting energy expenditure when NAE levels were elevated systematically by genetic ablation of fatty acid amide hydrolase or by subcutaneous infusion of synthetic NAE (63). In that study, NAE levels were significantly elevated both in plasma and in the brain.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Of note, our finding that elevations of NAEs in the liver corresponded with slightly increased resting energy expenditure contrasts with a recent study that found decreased resting energy expenditure when NAE levels were elevated systematically by genetic ablation of fatty acid amide hydrolase or by subcutaneous infusion of synthetic NAE (63). In that study, NAE levels were significantly elevated both in plasma and in the brain.…”
Section: Discussioncontrasting
confidence: 56%
“…The elevated brain NAE levels corresponded with reduced mRNA expression of thyrotropin-releasing hormone in the hypothalamus and thyroidstimulating hormone in the pituitary gland and with increased mRNA expression of deiodinase 2 in the hypothalamus. These changes resulted in lower circulating levels of triodothyronine (T 3 ) and thyroxine (T 4 ) and therefore decreased energy expenditure (63). Thus, the failure of the bacterially synthesized NAPE metabolites to reach the systemic circulation and the CNS may be somewhat beneficial, as this minimizes the likelihood that they will induce counterregulatory effects on energy expenditure in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Animal care was in compliance with the IASP and European Community (EC L358/1 18/12/86) guidelines on the use and protection of animals in experimental research. Animals were randomly divided into the following groups (n=10 each): non-colitic control group; colitic group; colitic groups receiving daily PEA 2, 10 or 50 mg/kg, respectively25 26; colitic group receiving daily PEA (10 mg/kg) and selective PPARα antagonist MK866 (10 mg/kg); colitic group receiving daily PEA and selective PPARγ antagonist GW9662 (1 mg/kg); internal control colitic group receiving daily PPARα or PPARγ antagonist, respectively27; non-colitic group receiving daily PEA 10 mg/kg (as drug internal control). Colitis was induced by administrating 4% DSS (MP Biomedicals, Solon, Ohio, USA) in drinking water for six consecutive days, as described in figure 1A.…”
Section: Methodsmentioning
confidence: 99%
“…Although this has not been demonstrated in the hypothalamus, CRH in the PVN is a known regulator of feeding behavior and may work through a similar mechanism to alter feeding behavior by regulating eCB levels in the PVN. Interestingly, FAAH knockout mice display reduced energy expenditure (Brown et al, 2012), which indicates that FAAH may play a direct role in energy metabolism. Pregastric neurons in the PVN that control gastric motility are subject to control by eCBs, which is likely to be mediated by AEA since both CB 1 and TRPV1 receptors are implicated (Boychuk, Zsombok, Tasker, & Smith, 2013) and AEA targets both receptors, whereas 2-AG binds only to CB 1 receptors.…”
Section: Crh Trh and Endocannabinoid Regulation Of Energy Homeostasismentioning
confidence: 99%